Akuntabilitas Pengelolaan Keuangan Desa Melalui Aplikasi Sistem Keuangan Desa (Siskeudes) - Riana, Arisma Desy; Mursyidah, Lailul (Jurnal Ilmiah Administrasi Publik, 2025)
Village financial management is an important aspect of village development in Indonesia.  In realizing the transparency and accountability of village governance, the Village Financial System Application (Siskeudes) was developed as a technological innovation to improve effectiveness, efficiency, and accountability in village financial governance.  This study aims to analyze the accountability of village financial management through the application of the Village Financial System Application (Siskeudes) in Keper Village, Krembung District, Sidoarjo Regency. The research method used is descriptive qualitative, with data collection through interviews and observations.  The results showed that the implementation of Siskeudes has improved village financial accountability in three main aspects, namely timely routine reporting, financial accountability in the form of measurable nominal, and proof of governance in accordance with regulations. These three indicators show that the use of Siskeudes in Keper Village is running very well. However, there are still obstacles in the form of lack of integration between the Siskeudes application and BPR Delta Artha Bank in Sidoarjo Regency.